Tăng trưởng kinh tế và ô nhiễm môi trường – Nghiên cứu thực nghiệm ở các nước ASEAN - Phạm Vũ, Thắng; Bùi Tú, Anh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
This paper aims to investigate whether ASEAN countries pursuing economic growth policy may destroy or improve their environment based on the Environment Kuznets Curve (EKC) hypothesis. The panel data of 10 ASEAN countries over the period of 1990–2017 is used to analyse the empirical relationship between environmental pollution and economic growth with other factors namely FDI, energy, population, and urbanisation in the region. The empirical result shows that overall the economic growth of ASEAN countries raised to their environmental pollution. The result of each country shows that Philipines, Vietnam, Laos, Myanmar, and Cambodia lied on the left-hand side of the EKC curve, meaning that their economic growth would lead to their environmental degradation. The other ASEAN countries are located on the right-hand side of the curve, in other words, their economic growth would improve their environment.